Evaluating New York City's Smoke‐Free Parks and Beaches Law: A Critical Multiplist Approach to Assessing Behavioral Impact. Issue 1 (26th May 2012) - Johns, Michael; Coady, Micaela H.; Chan, Christina A.; Farley, Shannon M.; Kansagra, Susan M.
Abstract: This article describes the evaluation of the law banning smoking in New York City's parks and beaches that went into effect in 2011. We discuss the practical and methodological challenges that emerged in evaluating this law, and describe how we applied the principles of critical multiplism to address these issues. The evaluation uses data from three complementary studies, each with a unique set of strengths and weaknesses that can provide converging evidence for the effectiveness of the law. Results from a litter audit and an observational study suggest the ban reduced smoking in parks and beaches. The purpose, methodology and baseline results from an ongoing survey that measures how frequently adults in NYC and across New York State notice people smoking in parks and on beaches are presented and discussed. Limitations are considered and suggestions are offered for future evaluations of similar policies.